A Descriptive Analysis of Mergers and Their Impact on Market Dynamics, Consumer Choices, and Industry Competitiveness - Shrestha, Laetitia; Sejuwal, Narendra (NPRC Journal of Multidisciplinary Research, 2024)
Background: Mergers in the insurance sector are a frequent occurrence, often promising operational efficiency and growth. However, their impact on employees remains a subject of debate, as these corporate transitions can significantly alter job roles, work dynamics, and employee satisfaction.Objective: This study aims to explore the effects of mergers on employees within the insurance industry, examining both the positive and negative consequences on job satisfaction, workload, and retention.Methods: A mixed-methods approach was employed, combining surveys and interviews with employees from various insurance firms that recently underwent mergers. The data was analyzed to identify key themes related to employee experiences, satisfaction levels, and the perceived impact of the mergers.Findings: The findings indicate a mixed response from employees, with some reporting positive changes such as career advancement opportunities and improved technology, while others expressed dissatisfaction with increased workload, reduced coordination, and a lack of involvement in decision-making. High turnover rates post-merger were also noted, suggesting concerns over job security and compensation.Conclusion: Mergers in the insurance sector have a complex effect on employees, with both beneficial and detrimental outcomes. Clear communication, employee involvement, and proper workload management are crucial to minimizing negative effects and improving overall satisfaction.Novelty: This study provides new insights into the nuanced impact of mergers on employee well-being, highlighting specific factors such as involvement in decision-making and post-merger compensation that have not been extensively covered in previous research.